Association of vitamin D, B-12 and Calcium levels in middle age women presenting with body aches and pains Vitamin D, B-12 and Calcium levels in aches and pains - Syed Sarosh Jamal Peerzada; Khurram Haq Nawaz; Muhammad Zahid Hussain; Hamad Khan; Syed Umer Shah; Hamid Mukhtar Butt (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association of vitamin D, B-12 and Calcium levels in middle age women presenting with body aches and pains Study Design: Comparative cross-sectional study Place and Duration of Study: General medicine department, Pak Emirates Military Hospital Rawalpindi. July 2019 to Feb 2020 Methodology: One fifty middle age women presenting with generalized aches and pains and not fulfilling criteria of any medical or psychiatric illness were included in the study. Equal number of matched controls were included from the community without having any aches and pains.Vitamin D, B-12 and Calcium levels were assessed in all the participants including the cases and controls. Body mass index and the Vitamin D, B-12 and Calcium levelswere compared among the cases and controls with chi-square. Results: Out of 150patients presenting with aches and pains, 91(60.6%) showed the presence of vitamin D deficiency, 60(40%) showed B12 deficiency and 56(37.3%) showed hypocalcemia. Among the healthy controls 61(40.6%) haddeficiency of vitamin D, 45(30%) had B12 deficiency and 32(21.3%) had hypocalcemia.After applying the chi-square test, we found that Vitamin D and calcium levelshad significant difference among the cases and controls (p-value<0.05). Conclusion: Calcium and vitamin D deficiencies emerged as predictors of aches and pains among the middle age women without any medical or psychiatric diagnosis.Incorporation of these investigations while evaluating the women for generalized aches and pains may be useful practice.